Real bonus card from Shariah perspective - Oziev, Gapur (s.n, 2012)
This study aims at critical examination of the concept of real bonus card from Shariah perspective. It is a relevantly new concept particularly in Malaysia market which is why almost nothing is written by Shariah scholars on it. According to the promoters of this programme it has a paid up capital of RM1 million and it is set to become Malaysia's leading cross-merchant consumer rewards program. The program is managed by Real Bonus Worldwide Sdn. Bhd. However, in this research project we will focus mostly on so called real bonus card which are part a of rewards programme. This concept should be studied from shariah perspective because it is dealing with money, rewards, bonuses and many other commercial activities which were not available in previous times